2019
DOI: 10.5056/jnm19059
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Prospective Study of Laparoscopic Nissen Fundoplication for Gastroesophageal Reflux Disease in Korea

Abstract: Backgrounds/AimsThis multicenter study aims to evaluate the effect and feasibility of anti-reflux surgery compared with medical treatment for gastroesophageal reflux disease (GERD). MethodsPatients with GERD who were undergoing medical treatment with proton pump inhibitors for more than 8 weeks and those who were scheduled to undergo anti-reflux surgery were enrolled. Efficacy of pre-operative medical treatment was evaluated retrospectively and effect of anti-reflux surgery was prospectively evaluated at 1 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
1
10
0
2
Order By: Relevance
“…The model was developed using Microsoft Excel. This study is an economic evaluation using secondary data (data that have already been collected and available from our previous researches), 14,15 therefore, informed consent could not be obtained from each patient. This study was approved by the Institutional Review Board of Kosin University Gospel Hospital (IRB No.…”
Section: Model Designmentioning
confidence: 99%
“…The model was developed using Microsoft Excel. This study is an economic evaluation using secondary data (data that have already been collected and available from our previous researches), 14,15 therefore, informed consent could not be obtained from each patient. This study was approved by the Institutional Review Board of Kosin University Gospel Hospital (IRB No.…”
Section: Model Designmentioning
confidence: 99%
“…As the authors already stated, the study by Park et al 18 has a limitation of reporting only short-term outcomes of laparoscopic Nissen fundoplication. Nevertheless, this study, which included the largest prospective cohort in Korea, may provide a better understanding of the efficacy of laparoscopic Nissen fundoplication in East Asian patients with GERD.…”
mentioning
confidence: 99%
“…In this issue of the Journal of Neurogastroenterology and Motility, Park et al 18 reported a multicenter prospective study on the efficacy of laparoscopic Nissen fundoplication for GERD in Korea. In the study, antireflux surgery was found to significantly improve GERD symptoms and quality of life in patients with GERD indicated for surgical treatment.…”
mentioning
confidence: 99%
“…4,5 Recently, the interest in managing GERD surgically has increased. [6][7][8] A recent randomized-controlled trial showed that laparoscopic Nissen fundoplication was superior to medication in reducing reflux-related heartburn. 6 In the study, treatment success, which was defined as an improvement of 50% or more in the GERD-Health Related Quality of Life score, was achieved in 67% of patients who underwent surgery, while 28% of patients who received active medical therapy including omeprazole and baclofen achieved treatment success.…”
mentioning
confidence: 99%
“…6 In another recent study in an Asian population, laparoscopic Nissen fundoplication was shown to be effective in patients for whom medical treatment was ineffective or who were unable to discontinue medication due to symptom recurrence. 7 Although medication should be the first-line treatment for patients with GERD and even though a large proportion of patients can be medically managed, anti-reflux surgery may offer an option for selected patients. 6 The efficacy of anti-reflux surgery in the management of GERD patients is well-recognized.…”
mentioning
confidence: 99%